Farmer Education and Potato Storage in Sri Lanka: Present Status and Future Prospects - Shanadi, A.T.; Samaraweera, G.C.; Wathugala, D.L; Indika, W.A.; Madushika, M.K.S. (University of Jaffna, 2020)
Potato is a highly demanded root crop in Sri Lanka while the land extent of potato cultivation is about 5,000 ha. The average annual production is around 80,000 metric tons. However, the year-round availability of potato is depending on industrial-scale storage and potato yield. Sri Lanka does not have a sound solution for potato storage problem yet. Therefore, the present study aims to identify the present situation of storage facilities and farmer education level on potato to reduce post-harvest losses and imports with the almost expanding potato market in off season. The study was based on primary data gathered through pre-structured questionnaires from 100 potato farmers selected using the snowball sampling technique. Out of 100 farmers, 48 farmers were selected from Nuwara-Eliya district and others were selected from Badulla district. Data analysis was done using descriptive and interracial statistics with support of minitab-16 software. Results indicated that, there are strong relationships with farmer education level between availability of the storage facilities (p value=0.000), farmer willingness to store potato (p-value=0.000) and neediness for convenient storage facilities (p-value=0.005). Educated farmers are most like to store potatoes to use during off season. However, majority (76%) of farmers do not have convenient storage facilities. Therefore, most (46%) of them never store potatoes and sell total harvest at lower price as soon as possible from harvested date. However, 87% of them need convenient storage facilities. Therefore, the present study has clearly brought out the urgency of convenient storage facilities for potato in order to expand potato market. Most importantly, appropriate knowledge delivery method while enhancing the education status is needed to encourage potato storage in Sri Lanka which ensures food security and poverty reduction. This further helps to reduce post-harvest losses and potato imports in Sri Lanka. Also, this study will be continued to identify the effect of other factors on the potato storage.
Keywords: Convenient storage facilities; Education level; Post-harvest losses; Potato cultivation